PENGARUH TINGKAT PENDAPATAN DAN NIAT MENGHINDARI PEMBOROSAN MAKANAN (FOOD WASTE) TERHADAP KERUGIAN EKONOMI PADA RUMAH TANGGA DI KABUPATEN SLEMAN - Anggrasari, Herdiana; Putri, Trisna Wahyu Swasdiningrum; Perdana, Putri; Cahyasita, Dhika (LPPM Universitas Malikussaleh - Indonesia, 2025)
The purpose of this study was to analyze the effect of income level and intention on food waste. In addition, analyzing economic losses due to food waste. The study was conducted in Sleman Regency in 2023. The number of respondents used was 40 respondents who managed food consumption in the household. Sampling was carried out using simple random sampling for 2 weeks. The analysis method used is a descriptive method to explain the current phenomenon related to food waste in Sleman Regency. The data analysis method used for the first purpose is to use a simple regression analysis method which is analyzed using eviews 12. The second purpose uses excel to calculate economic losses, while energy and carbohydrate losses are calculated using nutrisurvey 2007. The results of the study showed that household income levels and the intention to avoid food waste affect the level of food waste. During one year, the loss caused by food waste reached IDR 201,600 per year. Efforts to avoid the level of food waste can be done through socialization and campaigns for public awareness regarding consumer attitudes towards food ingredients and how to manage leftover food waste.